INHERITANCE WITH DIFFERENT RELIGIONS IN COUNTER LEGAL DRAFT OF ISLAMIC LAW COMPILATION: LEGAL EPISTEMOLOGICAL ANALYSIS - Ahmad Irfan (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2020)
Islamic inheritance in Counter Legal Draft of Islamic Law Compilation (CLD-KHI) is still an unfinished discussion. Legal reconstruction and contextualization in the modern era have made CLDK interesting to be raised to the surface. Reformulation of Islamic law in various legal constructs seems to be reviewed. This can be seen in several courts, even in jurisprudence that has provided opportunities for an inheritance to non-Muslims. This study is classified as a literature study, which focuses on legal epistemology based on Islamic inheritance in CLDK. This study found that religious differences as a barrier to the inheritance process have maqashid al-shariah in Islam and the value of justice and humanity. Correspondingly, critical and in-depth elaboration of the study of the epistemology of the inheritance law of different religions needs to continue to be developed towards a more comprehensive and constructive paradigm and renewal. Thus, the direction and purpose of Islamic law do not release the essential values that have become the spirit of Islam. This study implies that in the formation of human souls. They are able to portray themselves ideally as the caliph of Allah, on the face of the earth, which always has a sensitivity to every gap and structural and cultural injustice and to realize Islam as rahmatan li al-‘alamin (mercy to the worlds). That needs to be realized in the nine priorities (nawacita) of inheritance law in the establishment of inheritance law in Indonesia.Keywords: Legal Epistemology, Inheritance with different religion, CLD-KHI.